LILRB4 expression in chronic myelomonocytic leukemia and myelodysplastic syndrome based on response to hypomethylating agents. Issue 6 (11th May 2020) - Chien, Kelly S.; Class, Caleb A.; Montalban-Bravo, Guillermo; Wei, Yue; Sasaki, Koji; Naqvi, Kiran; Ganan-Gomez, Irene; Yang, Hui; Soltysiak, Kelly A.; Kanagal-Shamanna, Rashmi; Do, Kim-Anh; Kantarjian, Hagop M.; et al.
Abstract: LILRB4 is expressed in AML M4/M5 cells and negatively regulates immune cell activation via T-cell suppression. Its expression and role in chronic myelomonocytic leukemia (CMML) and myelodysplastic syndrome (MDS) are unknown. We investigated LILRB4 expression in 19 CMML and 27 MDS patients and correlated it with response to subsequent hypomethylating agent (HMA) therapy. LILRB4 RNA expression was increased in CMML patients when compared to MDS patients and healthy controls ( q  < 0.1) and slightly increased in patients who responded to HMAs ( q  > 0.1). Pathway analysis revealed upregulation of PD-1 signaling, CTLA-4 signaling, and inflammatory response, and gene correlates were positively associated with CTLA-4 expression. Given current modest results with immunotherapy in myeloid malignancies, further investigation of LILRB4 as an immune checkpoint inhibitor target is needed. With the positive correlation between LILRB4 and CTLA-4 expression, combining anti-LILRB4 and anti-CTLA-4 agents may be a novel therapeutic approach in myeloid malignancies that warrants larger studies.